Pancreatic gangliocytic paraganglioma harboring lymph node metastasis: a case report and literature review - Keisuke Nonaka; Yoko Matsuda; Akira Okaniwa; Atsuko Kasajima; Hironobu Sasano; Tomio Arai (BMC, 2017)
Abstract Background Gangliocytic paraganglioma (GP) is a rare neuroendocrine neoplasm, which occurs mostly in the periampullary portion of the duodenum; the majority of the reported cases of duodenal GP has been of benign nature with a low incidence of regional lymph node metastasis. GP arising from the pancreas is extremely rare. To date, only three cases have been reported and its clinical characteristics are largely unknown. Case presentation A nodule located in the pancreatic head was incidentally detected in an asymptomatic 68-year-old woman. Computed tomography revealed 18-, 8-, and 12-mm masses in the pancreatic head, the pancreatic tail, and the left adrenal gland, respectively. Subsequent genetic examination revealed an absence of mutations in the MEN1 and VHL genes. Macroscopically, the tumor located in the pancreatic head was 22 mm in size and displayed an ill-circumscribed margin along with yellowish-white color. Microscopically, it was composed of three cell components: epithelioid cells, ganglion-like cells, and spindle cells, which led to the diagnosis of GP. The tumor was accompanied by a peripancreatic lymph node metastasis. The tumor in the pancreatic tail was histologically classified as a neuroendocrine tumor (NET) G1 (grade 1, WHO 2010), whereas the tumor in the left adrenal gland was identified as an adrenocortical adenoma. The patient was disease-free at the 12-month follow-up examination. Conclusions Pancreatic GP is associated with a higher incidence of metastasis and larger tumor size than duodenal GPs, suggesting that the primary organ of GP is an important prognostic factor.